2010
DOI: 10.1021/jm1004368
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule Inhibitors of NADPH Oxidase 4

Abstract: NOX enzymes are the major contributors in many oxidative damage related diseases. Unfortunately, at present no specific NOX inhibitor is available. Here, we describe the discovery and development of novel NOX4 inhibitors. Compound libraries were tested in a cell-based assay as a primary screen, monitoring H2O2 production. Twenty-four compounds inhibited Nox4 activity with low-micromolar IC(50) values of which three were selected for further drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 22 publications
(40 reference statements)
0
41
0
1
Order By: Relevance
“…However, until recently, specific pharmacological inhibitors of NADPH oxidase were not available. For example, diphenyleneiodonium is commonly used as a synthetic NADPH oxidase inhibitor (34). However, diphenyleneiodonium nonspecifically inhibits the action of multiple flavoprotein dehydrogenases (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, until recently, specific pharmacological inhibitors of NADPH oxidase were not available. For example, diphenyleneiodonium is commonly used as a synthetic NADPH oxidase inhibitor (34). However, diphenyleneiodonium nonspecifically inhibits the action of multiple flavoprotein dehydrogenases (35).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, selective targeting of Nox2 may provide a novel therapeutic strategy for mitigation of ROS/RNS and cardiotoxic side effects, while maximizing its antitumor efficacy (56). To date, only a limited number of Nox isoform-selective inhibitors are available (57,58). This is due in part to serious limitations of the existing ROS/RNS assays as described below.…”
Section: Hts/ros/rns Assay-ros/rnsmentioning
confidence: 99%
“…In a recent study, Borbely et al (16) showed the methodical development of derivatives of primary hits obtained by an HTS campaign that searched for smallmolecule inhibitors of Nox4. The most potent compounds belong to the following core structures: oxalyl hydrazides, flavonoids, oxindoles, benzoquinolines, and benzothiophenes.…”
Section: Ebselenmentioning
confidence: 99%